A Literature Review on The Use of Music in Architectural Design Education - ÖLGEN, Burcu (Design and Technology Education: An International Journal, 2020)
In order to improve creative thinking in architectural design education, it is useful to interact with other disciplines such as music. There are many works of this interdisciplinary approach between architecture and music in the literature. These studies focus on new methods of creating forms with music for basic architectural education. The common aim is using music as a creative perspective for designing forms before proceeding to architectural design. Various structural forms designed by students are examined within these studies. It is concluded that designing with music could improve students’ imagination and could be benefit to architectural design education. Furthermore, these approaches could be improved, not only in basic form design, but also to be applied in an entire architectural project from space to façade. Music could be used as an inspiration to be transformed into a product, an interior or an architectural structure, and this could be useful for architectural design studio courses. Therefore, this review aims to underline the benefit of music in architectural education by examining the existing studies in the field, and it is a preliminary research for the further study of a method of designing with music.